Resolving Point Defects in the Hydration Structure of Calcite (10.4) with Three-Dimensional Atomic Force Microscopy - Söngen, H.; Reischl, Bernhard; Miyata, K.; Bechstein, R.; Raiteri, Paolo; Rohl, Andrew; Gale, Julian; Fukuma, T.; Kühnle, A. (The American Physical Society, 2018)
It seems natural to assume that defects at mineral surfaces critically influence interfacial processes such as the dissolution and growth of minerals in water. The experimental verification of this claim, however, is challenging and requires real-space methods with utmost spatial resolution, such as atomic force microscopy (AFM). While defects at mineral-water interfaces have been resolved in 2D AFM images before, the perturbation of the surrounding hydration structure has not yet been analyzed experimentally. In this Letter, we demonstrate that point defects on the most stable and naturally abundant calcite (10.4) surface can be resolved using high-resolution 3D AFM - even within the fifth hydration layer. Our analysis of the hydration structure surrounding the point defect shows a perturbation of the hydration with a lateral extent of approximately one unit cell. These experimental results are corroborated by molecular dynamics simulations.